Perform the complex number multiplication: (2 + 3i)(9 - 8i)

The formula for this using the FOIL method is: (a * c) + (b * c) + (a * d) + (b * d) where:

a = 2, b = 3, c = 9, and d = -8

(2 + 3i)(9 - 8i) = (2 * 9) + (3i * 9) + (2 * -8i) + (3i * -8i)

(2 + 3i)(9 - 8i) = 18 + 27i - 16i - 24i

(2 + 3i)(9 - 8i) = 18 + (27 - 16)i - 24i

(2 + 3i)(9 - 8i) = 18 + 11i - 24i

i

(2 + 3i)(9 - 8i) = 18 + 11i - 24* (-1)

(2 + 3i)(9 - 8i) = 18 + 11i + 24

(2 + 3i)(9 - 8i) = (18 + 24) + 11i

(2 + 3i)(9 - 8i) =